2021
DOI: 10.1007/s41315-021-00201-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial multi-link flexible manipulator arms based on system modes

Abstract: Industrial demand for high precision manipulators has lead to heavy, stiff, and therefore, expensive, inefficient, and potentially dangerous serial arm manipulators. The move towards lighter, and therefore, flexible manipulators has not matured, although there have been advancements in data processing capabilities, sensor technology, and control theory in the past couple of decades that could potentially reduce the problems with flexible serial manipulators. Most research in the past has focused on single link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this approach, a flexible link is segmented into elementary units, which are then interconnected at designated points. Each of these units is defined by an equation, formulated through an approximation method such as polynomial interpolation [84]. Compiling these equations results in a dynamic model of the whole flexible-link system.…”
Section: ) Assumed Mode Methods (Amm)mentioning
confidence: 99%
“…In this approach, a flexible link is segmented into elementary units, which are then interconnected at designated points. Each of these units is defined by an equation, formulated through an approximation method such as polynomial interpolation [84]. Compiling these equations results in a dynamic model of the whole flexible-link system.…”
Section: ) Assumed Mode Methods (Amm)mentioning
confidence: 99%
“…To the best of the author's understanding, it has been observed that little attempt has yet been made to exploit the inherent dynamics and vibration characteristics due to flexibility in the links and joints and resultant position inaccuracy [4,[22][23][24][26][27] for long-reach manipulators. Authors in [7,9] considered a robotic system of n-flexible-link robot connected by n revolute joints and assumed that the links can undergo a large overall rigid motion, however, the elastic deformation is considerably ignored whereas the present work for the first time, offers an analytical model of a spatial multi-link flexible manipulator manoeuvring in 3-D space with prismatic and revolute joints mounted on a mobile platform.…”
Section: Introductionmentioning
confidence: 99%
“…The present analysis deals with complicated coupled governing equations to represent transverse vibration characteristics of flexible links. Authors [24,26] considered a rigid-flexible spatial manipulator having one flexible link as compared to what is being presented here a spatial robotic system with flexible links and joints mounted on a mobile platform. Further, the system responses such as joint angular position and link residual vibration due to sinusoidal and bang-bang torque profiles have been graphically delineated to exploit the system dynamic characteristics while tracing the desired trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional rigid robotic arms [23] are heavy, expensive, inefficient, and even potentially dangerous, and researchers are favoring lightweight, flexible, flexibly linked robotic arms with soft joints or flexible parts that mimic living organisms [24][25]. Furthermore, in order to improve obstacle avoidance and self-adaptive capabilities, identify and place targets, and enable closed-loop control of the robotic arm to carry out the precise operation, redundant robotic arms [26] and machine vision technologies are introduced [27].…”
Section: Introductionmentioning
confidence: 99%